Developing Standardised Frameworks for the Successful Delivery of Public Private Partnership (PPP) Infrastructure Projects in Indonesia - Maryouri, Leny Anna Watie (Curtin University, 2017)
Infrastructure development requires substantial investment in a sustainable financing system. This thesis investigates the significant factors for the government, financier, private sector, State Owned Enterprise and consultant to make investment decisions in PPP infrastructure projects. Using a triangulation methodology, the findings from this thesis are PPP infrastructure frameworks for Indonesia that will guide and accelerate the process of risk allocation and distribution negotiation. This study contributes to improve government policy to accelerate infrastructure delivery.